Role of Neutrophil Extracellular Traps and Vesicles in Regulating Vascular Endothelial Permeability - Ma, Yonggang; Yang, Xiaoyuan; Chatterjee, Victor; Meegan, Jamie E.; Beard Jr., Richard S.; Yuan, Sarah Y. (Frontiers in Immunology, 2019)
The microvascular endothelium serves as the major barrier that controls the transport of blood constituents across the vessel wall. Barrier leakage occurs during infection or sterile inflammation, allowing plasma fluid and cells to extravasate and accumulate in surrounding tissues, an important pathology underlying a variety of infectious diseases and immune disorders. The leak process is triggered and regulated by bidirectional communications between circulating cells and vascular cells at the blood-vessel interface. While the molecular mechanisms underlying this complex process remain incompletely understood, emerging evidence supports the roles of neutrophil-endothelium interaction and neutrophil-derived products, including neutrophil extracellular traps and vesicles, in the pathogenesis of vascular barrier injury. In this review, we summarize the current knowledge on neutrophil-induced changes in endothelial barrier structures, with a detailed presentation of recently characterized molecular pathways involved in the production and effects of neutrophil extracellular traps and extracellular vesicles. Additionally, we discuss the therapeutic implications of altering neutrophil interactions with the endothelial barrier in treating inflammatory diseases.